Integration of digital technologies into the quality management system of construction production - Novak , Yevhenia (Ways to Improve Construction Efficiency, 2025)
The current problems of quality management in construction production in the context of digital transformation of the industry, increasing complexity of organizational and technological processes and increasing requirements for the quality of construction products, compliance with the cost and deadlines for the implementation of construction projects are considered. It is substantiated that traditional approaches to quality management, based mainly on post-factum control and fragmentary use of information, do not provide an adequate level of control over construction processes and do not allow timely prevention of defects, rework and deviations from design solutions. The purpose of the study is to substantiate and develop scientific and methodological approaches to the integration of digital technologies into the quality management system of construction production with the formation of a digitally integrated system that ensures continuous quality control at all stages of the life cycle of a construction object. The methodological basis of the study is the system, process and risk-oriented approaches, which allow considering quality as a dynamic result of the interaction of managerial, organizational and technological solutions. The paper improves the methodological provisions of the interaction of the quality management system with organizational and technological processes of construction through their digital coordination. The sequence of stages of the implementation of the scientific and methodological approach to the formation of a digitally integrated quality management system is proposed, which ensures the synchronization of quality requirements with the processes of planning and execution of construction work, and also creates conditions for the transition from reactive to proactive quality management. Particular attention is paid to the risk-oriented approach as a tool for preventing defects and reducing uncertainty in managerial decisions. Practical recommendations are formulated for the implementation of digital technologies in the quality management system of construction enterprises, taking into account regulatory and standardization requirements. The results of the study show that the application of the proposed approach contributes to increasing the stability of construction product quality indicators, reducing the risks of repeated work, optimizing construction deadlines and increasing the efficiency of construction production management in the context of digitalization.